Venetoclax with azacitidine or decitabine in patients with newly diagnosed acute myeloid leukemia: Long term follow‐up from a phase 1b study. Issue 2 (10th November 2020) - Pollyea, Daniel A.; Pratz, Keith; Letai, Anthony; Jonas, Brian A.; Wei, Andrew H.; Pullarkat, Vinod; Konopleva, Marina; Thirman, Michael J.; Arellano, Martha; Becker, Pamela S.; Chyla, Brenda; Hong, Wan‐Jen; et al.
Abstract: This analysis represents the longest‐term follow‐up for patients with acute myeloid leukemia (AML) treated with 400 mg of venetoclax plus azacitidine or decitabine. Adults with newly diagnosed AML ineligible for intensive chemotherapy were enrolled in an open‐label, non‐randomized, multicenter phase 1b trial of venetoclax with azacitidine (AZA; 75 mg/m 2 ; days 1‐7) or decitabine (DEC; 20 mg/m 2 ; days 1‐5). Endpoints included safety, response rates (complete remission [CR], CR with incomplete blood count recovery [CRi]), response duration and overall survival (OS). The median follow‐up time was 29 and 40 months for patients treated with venetoclax plus AZA and DEC combinations, respectively. Key Grade ≥ 3 AEs (AZA and DEC) were febrile neutropenia (39% and 65%), anemia (30% and 26%), thrombocytopenia (25% and 23%), and neutropenia (20% and 10%). The CR/CRi rate was 71% for venetoclax plus AZA and 74% for venetoclax plus DEC. The median duration of CR/CRi was 21.9 months and 15.0 months, and the median OS was 16.4 months and 16.2 months, for venetoclax plus AZA and DEC, respectively. These results support venetoclax plus hypomethylating agents as highly effective frontline AML therapies for patients unfit for intensive chemotherapy.